2020
DOI: 10.21203/rs.3.rs-90252/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Melatonin as an endogenous hormone to slow down the exhaustion of ovarian follicle reserve in mice–a novel insight into its roles in early folliculogenesis and ovarian aging

Abstract: Previous studies have shown that long-term intake of exogenous melatonin can effectively delay ovarian aging, but the mechanism has not been fully elucidated. We observed that SNAT, the rate-limiting enzyme in the melatonin synthetic pathway, is localized in primordial and early follicle, and that granulosa cells isolated from follicle can synthesize melatonin. In vitro cultured neonatal mice ovaries with melatonin inhibited primordial follicle activation and early follicle growth. In vivo experiments further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…AKT1, which belongs to the AKT subfamily of serine/threonine kinases, is a multifunctional protein that regulates cell growth, survival, and proliferation (53). Emerging evidence has shown that melatonin can inhibit early follicle atresia and slow down the exhaustion of the ovarian follicle reserve by regulating the PI3K/ AKT pathway in mice (54). Similarly, Leung et al found that melatonin acts as a modulator of ovarian function and stimulates theca cell steroidogenesis by activating the PI3K/AKT pathway in bovine small follicles (55).…”
Section: Melatonin's Eight Hub Targets In Dormentioning
confidence: 99%
“…AKT1, which belongs to the AKT subfamily of serine/threonine kinases, is a multifunctional protein that regulates cell growth, survival, and proliferation (53). Emerging evidence has shown that melatonin can inhibit early follicle atresia and slow down the exhaustion of the ovarian follicle reserve by regulating the PI3K/ AKT pathway in mice (54). Similarly, Leung et al found that melatonin acts as a modulator of ovarian function and stimulates theca cell steroidogenesis by activating the PI3K/AKT pathway in bovine small follicles (55).…”
Section: Melatonin's Eight Hub Targets In Dormentioning
confidence: 99%